Application of artificial neural network to predict the wave characteristics to improve the sea waves and currents forces applied on the jacket platform legs - Yazid S. Alhodairy, Kabir Sadeghi (Journal of Pure & Applied Sciences, 2019)
It is essential for all offshore structures analysis to estimate the forces generated by the wave and current by developing a program for modeling wave and current forces on offshore structural members. This study investigates the possibility of utilizing the relatively current technique of artificial neural networks (ANN) to predict the wave characteristics. Besides, the comparison of ANN models with the most two widely used empirical models included Bretschneider and Sverdrup-Munk and Bretschneider (SMB) equations showed a better performance for ANN models rather than empirical models. Furthermore, a developed program was studied for calibration and comparison purposes, where the program was checked against well-known professional software package called Structural Analysis Computer System (SACS). Airy wave theory (linear theory) has been implemented in the present study to calculate the water particles kinematics. Also, the Morison equation was used for converting the velocity and acceleration terms into resultant forces.